PROPAGATION OF A HARMONIC WAVE IN A PLATE WITH SYMMETRIC STRUCTURE - Melkonyan, A.V.; Sarkisyan, S.V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2011)
In this paper a three-layer plate with symmetrical structure to solve the prob-lem of determining the properties of the middle layer, which can propagate the harmonic wave in three-layer plate with phase speed equal to the phase speed of a single-layer plate.